Silicon-carbon composite material and preparation method, negative electrode sheet and battery
By using silicon-carbon composite materials in lithium-ion batteries, the combination of grinding treatment and carbon cladding layer solves the problem of volume changes in graphite material and insufficient electron conduction performance, and improves the capacity retention and cycling performance of the battery.
Patent Information
- Application Number
- CN202411298818.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The graphite negative electrode material used in traditional lithium-ion batteries changes in volume during charging and discharging, resulting in poor material powdering and cycling performance, and insufficient electron conduction performance, making it difficult to meet the needs of high capacity and high rate performance.
Using the preparation method of silicon-carbon composite material, the silicon-carbon composite material is formed by mixing the silicon-active material and graphite material and grinding treatment, and carbon source gas is introduced into the heat treatment chamber to form a carbon cladding layer, which enhances the conductivity and Structural stability, alleviating the volume expansion of silicon material.
The capacity retention rate and charge-discharge specific capacity of the battery are significantly improved, the cycling performance is improved, and the stability and conductivity of silicon-carbon composite materials are enhanced.
Smart Images

Figure CN118811808B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a silicon-carbon composite material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] A battery is a device that can store and release electrical energy. Lithium-ion batteries are the most widely used battery system in commercial applications. Graphite is often used as the negative electrode material of lithium-ion batteries in traditional technology. However, the theoretical specific capacity of graphite can only reach 372mAh / g, which is gradually unable to meet the growing battery performance requirements.
[0003] The theoretical specific capacity of silicon can reach 4200mAh / g, making it an ideal candidate for negative electrode materials. However, the volume change of silicon during the charge and discharge process exceeds 300%, which can easily cause the silicon material to pulverize and fall off the current collector, resulting in poor battery cycle performance. Furthermore, the poor electronic conductivity of silicon materials not only limits the actual charge and discharge capacity of silicon materials, but also leads to poor charge and discharge rate performance of the battery. Some traditional technologies propose to mix silicon materials with carbon materials to form silicon-carbon materials to improve the performance of single silicon materials, but the traditional silicon-carbon materials still have poor inhibitory effects on the volume expansion of silicon materials, resulting in low cycle performance of batteries using the silicon-carbon materials. Summary of the invention
[0004] Based on this, it is necessary to provide a method for preparing a silicon-carbon composite material to address the problems in the above-mentioned background technology. The silicon-carbon composite material prepared by the method can more effectively inhibit the volume expansion of the silicon material during the charging and discharging process, so that the battery using the silicon-carbon composite material has a higher capacity retention rate.
[0005] In a first aspect, the present disclosure provides a method for preparing a silicon-carbon composite material, which comprises the following steps:
[0006] Mixing graphite material and silicon active material with a particle size of micrometers or above and grinding them to form a silicon-carbon composite material; and
[0007] The silicon-carbon composite material is placed in a heat treatment chamber, a carbon source gas is introduced into the heat treatment chamber, and the temperature of the heat treatment chamber is controlled to decompose the carbon source gas to form a carbon coating layer on the surface of the silicon-carbon composite material.
[0008] In some embodiments of the present disclosure, in the silicon-carbon composite material formed after grinding, the thickness of the silicon active material is 1 nm to 200 nm, and the length of the silicon active material is 20 nm to 5000 nm; and / or,
[0009] In the silicon-carbon composite material formed after the grinding process, the thickness of the graphite material is 1 nm to 200 nm, and the length of the graphite material is 200 nm to 15000 nm.
[0010] In some embodiments of the present disclosure, the silicon active material comprises single crystal silicon; and / or,
[0011] The graphite material includes one or more of artificial graphite and natural graphite.
[0012] In some embodiments of the present disclosure, the mass ratio of the silicon active material to the graphite material is (1.5~10):1.
[0013] In some embodiments of the present disclosure, the step of performing grinding treatment includes: using sand grinding to sequentially perform coarse grinding treatment and fine grinding treatment on the mixed silicon active material and the graphite material.
[0014] In some embodiments of the present disclosure, in the step of performing the grinding process, the time of the fine grinding process is 2 hours to 8 hours.
[0015] In some embodiments of the present disclosure, in the step of cracking the carbon source gas, the thickness of the formed carbon coating layer is 1 nm to 20 nm.
[0016] In a second aspect, the present disclosure further provides a silicon-carbon composite material, which is prepared by the method for preparing the silicon-carbon composite material as described in any of the above embodiments.
[0017] In a third aspect, the present disclosure further provides a negative electrode plate, which includes the silicon-carbon composite material according to any of the above embodiments.
[0018] In a fourth aspect, the present disclosure further provides a battery, which includes a positive electrode and a negative electrode arranged opposite to each other, and the negative electrode includes the negative electrode plate as described in the above embodiment.
[0019] In the preparation method of the silicon-carbon composite material disclosed in the present invention, the silicon active material and the graphite material are first mixed and then ground. This step utilizes the structural characteristics of the silicon active material and the graphite material, so that the graphite material moves along the 002 crystal plane during the grinding process to form a graphite sheet, and the silicon active material also forms a sheet structure, and the graphite sheet is in situ and closely attached to the surface of the silicon sheet along the thickness direction. In addition, after the silicon-carbon composite is formed, a carbon source gas is further used to form a carbon coating layer. The carbon coating layer can significantly enhance the electrical conductivity and structural stability between the graphite sheet and the silicon sheet. Through the combined effect of the sandwich structure of the graphite sheet and the silicon sheet and the carbon coating layer, the volume expansion of the silicon active material during the charge and discharge process can be effectively alleviated, and the stability of the silicon active material can be maintained, thereby greatly improving the capacity retention rate of the battery using the silicon-carbon composite material.
[0020] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of the steps of a method for preparing a silicon-carbon composite material disclosed in the present invention;
[0022] Figure 2 The test results of XRD test on the materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 3;
[0023] Figure 3 The surface morphology of the materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 3 was observed using a scanning electron microscope.
[0024] Figure 4 This is a cross-sectional morphology of the pole piece of Example 1 observed using a scanning electron microscope. DETAILED DESCRIPTION
[0025] To facilitate understanding of the present invention, a more comprehensive description of the present invention is provided below. The preferred embodiments of the present invention are given herein. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the content of the present invention more thorough and comprehensive.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this document pertains. The terms used herein in the specification of this document are only for describing specific embodiments and are not intended to limit this document.
[0027] It should be understood that when an element or layer is referred to as being "on, "adjacent to, "connected to, or "coupled to" another element or layer, it may be directly on, adjacent to, connected to, or coupled to the other element or layer, or there may be intervening elements or layers. In contrast, when an element is referred to as being "directly on, "directly adjacent to, "directly connected to, or "directly coupled to" another element or layer, there may be no intervening elements or layers. It should be understood that although the terms first, second, third, etc. may be used to describe various elements, components, regions, layers, and / or portions, these elements, components, regions, layers, and / or portions should not be limited by these terms. These terms are merely used to distinguish one element, component, region, layer, or portion from another element, component, region, layer, or portion.
[0028] Spatially relative terms such as "under," "beneath," "below," "under," "above," "above," and the like may be used herein for ease of description to describe the relationship of one element or feature to other elements or features. It should be understood that the spatially relative terms are intended to also include different orientations of the device in use and operation. For example, if the device in the accompanying drawings is flipped, then the elements or features described as "under other elements" or "under" or "under" will be oriented as "over" the other elements or features. Thus, the exemplary terms "under" and "under" may include both upper and lower orientations. The device may be otherwise oriented (e.g., rotated 90 degrees or other orientations) and the spatial descriptors used may be interpreted accordingly.
[0029] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be a limitation of the present disclosure. When used herein, the singular forms of "a", "an" and "the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0030] The present disclosure provides a method for preparing a silicon-carbon composite material, which comprises the following steps: mixing a silicon active material and a graphite material and then grinding them to form a silicon-carbon composite material. Also, placing the silicon-carbon composite material in a heat treatment chamber, introducing a carbon source gas into the heat treatment chamber, controlling the temperature of the heat treatment chamber so that the carbon source gas is cracked, and forming a carbon coating layer on the surface of the silicon-carbon composite material.
[0031] In the preparation method of the silicon-carbon composite material disclosed in the present invention, the silicon active material and the graphite material are first mixed and then ground. This step utilizes the structural characteristics of the silicon active material and the graphite material, so that the graphite material moves along the 002 crystal plane during the grinding process to form a graphite sheet, and the silicon active material also forms a sheet structure, and the graphite sheet is in situ and closely attached to the surface of the silicon sheet along the thickness direction. In addition, after the silicon-carbon composite is formed, a carbon source gas is further used to form a carbon coating layer. The carbon coating layer can significantly enhance the electrical conductivity and structural stability between the graphite sheet and the silicon sheet. Through the combined effect of the sandwich structure of the graphite sheet and the silicon sheet and the carbon coating layer, the volume expansion of the silicon active material during the charge and discharge process can be effectively alleviated, and the stability of the silicon active material can be maintained, thereby greatly improving the capacity retention rate of the battery using the silicon-carbon composite material.
[0032] Figure 1Schematic diagram of the steps of a method for preparing a silicon-carbon composite material disclosed in the present invention. Figure 1 As shown, the method for preparing the silicon-carbon composite material includes steps S1 to S3, which are specifically as follows.
[0033] Step S1, mixing silicon active material and graphite material.
[0034] It can be understood that in this embodiment, the particle size of the silicon active material should be above the micron level, and the silicon active material can form a sheet material with a thickness of nanometer or submicron level during the subsequent grinding process, so that it can be in situ and closely attached to the graphite sheet.
[0035] As an example of this embodiment, the silicon active material includes single crystal silicon. Compared with materials such as polycrystalline silicon and amorphous silicon particles, single crystal silicon and graphite materials are more likely to form a closely attached sandwich structure during the subsequent grinding process, so that the volume expansion of the finally formed silicon-carbon composite material is more significantly suppressed.
[0036] In some examples, single crystal silicon wafers or waste silicon ingots of solar cells may be used as silicon active materials.
[0037] As an example of this embodiment, the graphite material includes one or more of artificial graphite and natural graphite. Compared with artificial graphite, natural graphite has a more obvious effect of moving along the 002 crystal plane to form graphite sheets during the subsequent grinding process, and accordingly the performance of the silicon-carbon composite material finally formed is better.
[0038] As an example of this embodiment, the mass ratio of silicon active material to graphite material is (1.5~10):1. The silicon active material and graphite material of this mass ratio can more effectively exert the advantages of the high specific capacity of the silicon active material while ensuring a low volume expansion rate, so that the final silicon-carbon composite material has both a higher charge-discharge specific capacity and a higher capacity retention rate. If the mass proportion of the graphite material is too high, it will make it difficult to give full play to the advantages of the high specific capacity of the silicon active material, and the actual specific capacity of the silicon-carbon composite material will still be low, and the capacity retention rate will also be reduced.
[0039] In some examples, the mass ratio of the silicon active material to the graphite material is 1.5:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1, or the mass ratio of the silicon active material to the graphite material may be between any two of the above mass ratios.
[0040] As an example of this embodiment, the step of mixing the silicon active material and the graphite material includes: dispersing the silicon active material and the graphite material in a solvent to form a suspension, and then performing a homogenous dispersion treatment on the suspension. The homogenous dispersion treatment can be performed in a homogenizer.
[0041] In some examples, the solvent used includes one or more of methanol, ethanol, propanol, isopropanol, butanol, acetone, isopropyl alcohol, ethylene glycol, ether, n-hexane, n-heptane, N-methylpyrrolidone and kerosene. In this embodiment, the solvent is ethanol.
[0042] Step S2, grinding the mixed silicon active material and graphite material to form a silicon-carbon composite material.
[0043] In this embodiment, the grinding process can cut the silicon active material and the graphite material together to form a sheet material with a thickness of nanometer or submicron level, and thanks to the structural characteristics of the silicon active material and the graphite material themselves, the graphite material moves along the 002 crystal plane during the grinding process to form a graphite sheet, and the silicon active material also forms a sheet structure, and the graphite sheet is in situ and closely attached to the surface of the silicon sheet. Thus, the closely attached sandwich structure required by the present disclosure can be formed.
[0044] As an example of this embodiment, before the step of performing the grinding treatment, the silicon active material and the graphite material are dispersed in a solvent to form a suspension, and the entire suspension is subjected to the grinding treatment.
[0045] In some examples, the solvent used includes one or more of methanol, ethanol, propanol, isopropanol, butanol, acetone, isopropyl alcohol, ethylene glycol, ether, n-hexane, n-heptane, N-methylpyrrolidone and kerosene. In this embodiment, the solvent is ethanol.
[0046] As an example of this embodiment, the step of performing grinding treatment includes: using sand grinding to sequentially perform coarse grinding treatment and fine grinding treatment on the mixed silicon active material and graphite material. The sand grinding treatment can effectively cut the silicon active material and the graphite material together, and make the two closely attached in situ along the thickness direction during the cutting process. It can be understood that the main difference between the coarse grinding treatment and the fine grinding treatment is the particle size of the abrasive. Compared with the coarse grinding treatment, the particle size of the abrasive used in the fine grinding treatment is finer.
[0047] As an example of this embodiment, the coarse grinding process may be performed in a coarse grinder, and the fine grinding process may be performed in a fine grinder.
[0048] As an example of this embodiment, in the silicon-carbon composite material formed after the grinding process, the thickness of the silicon active material is 1 nm to 200 nm.
[0049] In some examples, the thickness of the silicon active material may be 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 70 nm, 100 nm, 120 nm, 150 nm, 200 nm, or the thickness of the silicon active material may be between any two of the above thicknesses.
[0050] As an example of this embodiment, in the silicon-carbon composite material formed after the grinding process, the length of the silicon active material is 20 nm to 5000 nm.
[0051] In some examples, the length of the silicon active material may be 20 nm, 100 nm, 200 nm, 300 nm, 500 nm, 1000 nm, 1500 nm, 2000 nm, 3000 nm, 5000 nm, or the length of the silicon active material may be between any two of the above lengths.
[0052] As an example of this embodiment, in the silicon-carbon composite material formed after the grinding process, the thickness of the graphite material is 1 nm to 200 nm.
[0053] In some examples, the thickness of the graphite material may be 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 70 nm, 100 nm, 120 nm, 150 nm, or 200 nm, or the thickness of the graphite material may be between any two of the above thicknesses.
[0054] As an example of this embodiment, in the silicon-carbon composite material formed after the grinding process, the length of the graphite material is 200 nm to 15000 nm.
[0055] In some examples, the length of the graphite material may be 200 nm, 300 nm, 500 nm, 1000 nm, 2000 nm, 3000 nm, 5000 nm, 7000 nm, 10000 nm, 12000 nm, 15000 nm, 20000 nm, or the length of the graphite material may be between any two of the above lengths.
[0056] As an example of this embodiment, in the silicon-carbon composite material formed after the grinding process, the length of the graphite material is greater than the length of the silicon active material.
[0057] It can be understood that the thickness and length of the silicon active material and the graphite material can be controlled accordingly by controlling the specific process conditions of the grinding treatment.
[0058] As an example of this embodiment, the time of the rough grinding process is 30 minutes to 120 minutes.
[0059] In some examples, the time of the rough grinding process is 30 minutes, 60 minutes, 90 minutes, or 120 minutes, or the time of the rough grinding process can also be between any two of the above times.
[0060] As an example of this embodiment, the time of the fine grinding process is 2 hours to 8 hours.
[0061] In some examples, the time of the fine grinding treatment is 2h, 3h, 4h, 5h, 6h, 7h, 8h, or the time of the fine grinding treatment can also be between any two of the above times. Among them, the fine grinding treatment has a more obvious effect on the morphology and performance of the silicon-carbon composite. Controlling the time of the fine grinding treatment helps to obtain a higher charge-discharge specific capacity and a higher cycle capacity retention rate. When the fine grinding time is short, the cycle capacity retention rate of the silicon-carbon composite material is low. When the fine grinding time is long, the charge-discharge specific capacity of the silicon-carbon composite material is low, and the cycle capacity retention rate is also reduced.
[0062] As an example of this embodiment, after the grinding process, a drying process is further included to remove the solvent and form a silicon-carbon composite material.
[0063] Step S3, forming a carbon coating layer on the surface of the silicon-carbon composite material.
[0064] In this embodiment, the silicon-carbon composite material is placed in a heat treatment chamber, a carbon source gas is introduced into the heat treatment chamber, and the temperature of the heat treatment chamber is controlled to decompose the carbon source gas to form a carbon coating layer.
[0065] As an example of this embodiment, before the carbon source gas is introduced, the silicon-carbon composite material can be sintered in a heat treatment chamber to reduce defects in the flaky graphite material and the flaky silicon active material and improve the adhesion stability between the flaky graphite material and the flaky silicon active material.
[0066] As an example of this embodiment, during the sintering process of the silicon-carbon composite material in the heat treatment chamber, the temperature of the heat treatment chamber can be controlled to be 600° C. to 800° C.
[0067] In some examples, during the sintering process, the temperature of the heat treatment chamber can be controlled to 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, or 800°C, or the temperature of the heat treatment chamber can be controlled between any two of the above temperatures.
[0068] As an example of this embodiment, during the sintering process, the sintering time is controlled to be 0.5h~6h.
[0069] In some examples, during the sintering process, the sintering time can be controlled to be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, or 6 h, or the sintering time can be controlled to be between any two of the above times.
[0070] As an example of this embodiment, during the sintering process of the silicon-carbon composite material in the heat treatment chamber, a protective gas is kept flowing into the heat treatment chamber.
[0071] In some examples, the protective gas includes one or more of argon and nitrogen.
[0072] As an example of this embodiment, the flow rate of the protective gas may be 300 sccm to 1000 sccm.
[0073] In some examples, the flow rate of the protective gas may be 300 sccm, 400 sccm, 500 sccm, 600 sccm, 700 sccm, 800 sccm, 900 sccm, or 1000 sccm, or the flow rate of the protective gas may be between any two of the above flow rates.
[0074] As an example of this embodiment, the carbon source gas includes one or more of acetylene, ethylene, methane, ethane, propane and n-butane. In this embodiment, acetylene is used as the carbon source gas.
[0075] As an example of this embodiment, in the step of cracking the carbon source gas, the temperature of the heat treatment chamber is controlled to be 600°C to 800°C.
[0076] In some examples, in the step of cracking the carbon source gas, the temperature of the heat treatment chamber can be controlled to 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, or 800°C, or the temperature of the heat treatment chamber can be controlled between any two of the above temperatures.
[0077] As an example of this embodiment, in the step of cracking the carbon source gas, the time for introducing the carbon source gas is controlled to be 0.5h~6h.
[0078] In some examples, in the step of cracking the carbon source gas, the time for introducing the carbon source gas can be controlled to be 0.5h, 1h, 2h, 3h, 4h, 5h, or 6h, or the time for introducing the carbon source gas can be controlled to be between any two of the above times.
[0079] As an example of this embodiment, in the step of cracking the carbon source gas, the flow rate of the introduced carbon source gas is controlled to be 300 sccm-1000 sccm.
[0080] In some examples, the flow rate of the carbon source gas may be 300 sccm, 400 sccm, 500 sccm, 600 sccm, 700 sccm, 800 sccm, 900 sccm, or 1000 sccm, or the flow rate of the carbon source gas may be between any two of the above flow rates.
[0081] As an example of this embodiment, the thickness of the formed carbon coating layer is 1 nm to 20 nm.
[0082] In some examples, the thickness of the formed carbon coating layer is 1 nm, 2 nm, 3 nm, 5 nm, 7 nm, 10 nm, 12 nm, 15 nm, or 20 nm, or the thickness of the formed carbon coating layer may be between any two of the above thicknesses.
[0083] It can be understood that through the above steps S1 to S3, a silicon-carbon composite material can be formed, and the silicon-carbon composite material can be used as a negative electrode active material of a battery.
[0084] On the other hand, the present disclosure further provides a silicon-carbon composite material, which is prepared by the preparation method of the silicon-carbon composite material in the above embodiment.
[0085] On the other hand, the present disclosure further provides a negative electrode plate, which includes the silicon-carbon composite material in the above embodiment.
[0086] Furthermore, the negative electrode plate includes a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector, and the negative electrode active layer includes the silicon-carbon composite material as described in any of the above embodiments.
[0087] As an example of this embodiment, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. Among them, in the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0088] As an example of this embodiment, the negative electrode active layer may further include one or more of a conductive agent and a binder.
[0089] In the negative electrode active layer, the conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, graphene and carbon nanofibers.
[0090] In the negative electrode active layer, the binder may be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose and a copolymer of styrene and butadiene.
[0091] On the other hand, the present disclosure further provides a battery, which includes a positive electrode and a negative electrode, the positive electrode and the negative electrode are arranged opposite to each other, and the negative electrode includes a negative electrode plate as described in any of the above embodiments.
[0092] As an example of this embodiment, the positive electrode may include a positive electrode sheet. The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer.
[0093] As an example of this embodiment, the positive electrode active layer includes a positive electrode active material selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, layered ternary positive electrode materials, spinel lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese phosphate and lithium cobalt phosphate.
[0094] As some examples of this embodiment, the positive electrode active layer may further include one or more of a conductive agent and a binder.
[0095] In the positive electrode active layer, the conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, graphene and carbon nanofibers.
[0096] In the positive electrode active layer, the binder may be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose and a copolymer of styrene and butadiene.
[0097] As an example of this embodiment, the battery may further include a separator, which is disposed between the positive electrode sheet and the negative electrode sheet.
[0098] As an example of this embodiment, the battery may further include an electrolyte, the electrolyte infiltrating the separator, the positive electrode active layer, and the negative electrode active layer.
[0099] On the other hand, the present disclosure further provides an electrical device, which includes a functional body and a battery as described in any of the above embodiments, wherein the battery is used to supply energy to the functional body.
[0100] As some examples of this embodiment, the power-consuming device may be a mobile phone, a laptop computer, a smart watch, or an electric car.
[0101] In order to facilitate understanding of the specific implementation methods and beneficial effects of the present disclosure, the present disclosure also provides the following more specific examples and comparative examples. Through the description of the examples and comparative examples, the beneficial effects of the present disclosure will also be more obvious.
[0102] Example 1
[0103] Preparation of silicon-carbon composite materials: Provide solar waste silicon ingots (single crystal silicon ingots), crush them into micron-sized powders as silicon active materials. Weigh 1000g of silicon active material and 200g of artificial graphite in ethanol, mix and homogenize. Put the suspension after mean dispersion treatment into a coarse grinder for sand grinding for 1h, then transfer it to a fine grinder for sand grinding for 5h, take it out and dry it to form a silicon-carbon composite. Put the silicon-carbon composite into a rotary kiln, pass nitrogen with a flow rate of 600sccm, heat it to 700℃ and keep it warm for 1h. Then pass acetylene with a flow rate of 600sccm, keep it warm at 700℃ for 1h to form a silicon-carbon composite material.
[0104] It has been determined that the silicon-carbon composite material contains silicon sheets and graphite sheets with a thickness of nanometers and a carbon coating layer on the surface of the two. The thickness of the silicon sheet is about 30nm, the length is about 500nm, and the width is about 150nm. The thickness of the graphite sheet is about 50nm, the length is about 5um, the width is about 1um, and the thickness of the carbon coating layer is 3nm. In the silicon-carbon composite material, the mass proportion of silicon alone is 79.3.wt%, the mass proportion of carbon alone is 18.8wt%, and the mass proportion of oxygen is 1.9wt%.
[0105] Preparation of negative electrode sheet: The composite negative electrode material, Super P and sodium alginate prepared above are dispersed in water at a mass ratio of 80:10:10 and stirred evenly to form a slurry. The slurry is scraped onto the surface of the copper foil and then dried to form a negative electrode sheet.
[0106] Preparation of electrolyte: A mixed solvent of EC and DMC in a volume ratio of 1:1 is used, and lithium hexafluorophosphate with a concentration of 1 mol / L is dissolved therein to form an electrolyte.
[0107] Prepare a half-cell: Pair the negative electrode sheet with the lithium sheet, use a three-layer film of PP / PE / PP as an isolation membrane to separate the negative electrode sheet and the lithium sheet, inject electrolyte, and form a button-type half-cell.
[0108] Example 2
[0109] The only difference between Example 2 and Example 1 is that Example 2 uses natural graphite instead of artificial graphite.
[0110] It has been determined that the silicon-carbon composite material contains silicon sheets and graphite sheets with a thickness of nanometers and a carbon coating layer on the surface of the two. The thickness of the silicon sheet is about 30nm, the length is about 500nm, and the width is about 150nm. The thickness of the graphite sheet is about 40nm, the length is about 4um, the width is about 1um, and the thickness of the carbon coating layer is 3nm. In the silicon-carbon composite material, the mass proportion of silicon alone is 78.9.wt%, the mass proportion of carbon alone is 19.3wt%, and the mass proportion of oxygen is 1.8wt%.
[0111] Example 3
[0112] The only difference between Example 3 and Example 1 is that in Example 3, the mass of the artificial graphite in preparing the silicon-carbon composite material is 100 g.
[0113] Example 4
[0114] The only difference between Example 4 and Example 1 is that in Example 4, the mass of artificial graphite in preparing the silicon-carbon composite material is 400 g.
[0115] Example 5
[0116] The only difference between Example 5 and Example 1 is that in Example 5, the mass of the artificial graphite in preparing the silicon-carbon composite material is 600 g.
[0117] Example 6
[0118] The only difference between Example 6 and Example 1 is that in Example 6, the mass of the artificial graphite in preparing the silicon-carbon composite material is 1000 g.
[0119] Example 7
[0120] The only difference between Example 7 and Example 1 is that in Example 7, the mass of the artificial graphite in preparing the silicon-carbon composite material is 2000 g.
[0121] Example 8
[0122] The only difference between Example 8 and Example 1 is that the fine grinding time in Example 8 when preparing the silicon-carbon composite material is 8 hours.
[0123] Example 9
[0124] The only difference between Example 9 and Example 1 is that the fine grinding time in Example 9 when preparing the silicon-carbon composite material is 6 hours.
[0125] Example 10
[0126] The only difference between Example 10 and Example 1 is that the fine grinding time in Example 10 when preparing the silicon-carbon composite material is 4 hours.
[0127] Embodiment 11
[0128] The only difference between Example 11 and Example 1 is that the fine grinding time in the preparation of the silicon-carbon composite material in Example 11 is 2 hours.
[0129] Example 12
[0130] The only difference between Example 12 and Example 1 is that in Example 12, single crystal silicon wafers are used instead of solar waste silicon ingots when preparing the silicon-carbon composite material.
[0131] Comparative Example 1
[0132] The only difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, nano silicon powder is used instead of solar waste silicon ingots when preparing the silicon-carbon composite material.
[0133] It has been determined that the silicon-carbon composite material contains graphite sheets with a thickness of nanometers, silicon nanoparticles, and a carbon coating layer on the surface of the two. The silicon nanoparticles are spherical and have a particle size of about 100nm. The graphite sheet is about 100nm thick, about 5um long, and about 1um wide, and the thickness of the carbon coating layer is 3nm. In the silicon-carbon composite material, the mass proportion of silicon alone is 79.8.wt%, the mass proportion of carbon alone is 19.6wt%, and the mass proportion of oxygen is 0.6wt%.
[0134] Comparative Example 2
[0135] The only difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, no artificial graphite is added when preparing the silicon-carbon composite material.
[0136] It has been determined that the prepared material contains a silicon wafer with a thickness of nanometers and a carbon coating on the surface, wherein the thickness of the silicon wafer is about 30nm, the length is about 500nm, and the width is about 150nm. The thickness of the carbon coating is 3nm. In the prepared material, the mass proportion of silicon alone is 92.5.wt%, the mass proportion of carbon alone is 5.3wt%, and the mass proportion of oxygen is 2.2wt%.
[0137] Comparative Example 3
[0138] The only difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, no silicon active material is added when preparing the silicon-carbon composite material.
[0139] The prepared material contains graphite sheets and a carbon coating on the surface, wherein the graphite sheets are about 300nm thick, about 8um long, about 2.4um wide, and rough. In the prepared material, the mass proportion of carbon is 99.5wt%, and the mass proportion of oxygen is 0.5wt%.
[0140] Test 1: XRD test was performed on the materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 3. The test results can be seen in Figure 2 .
[0141] Test 2: The surface morphology of the materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 3 was observed using a scanning electron microscope. The surface morphology can be seen at Figure 3 The cross-sectional morphology of the electrode prepared in Example 1 can be seen in Figure 4 .
[0142] Test 3: The half-cells of each embodiment and comparative example were charged and discharged at a constant current using a Blue Electric charge and discharge tester. The cut-off voltage was set to 0.01 V ~ 1.0 V, the rate was set to 0.2C, and the charge and discharge cycle was 100 times. The first week reversible capacity, the 100th week reversible capacity, the cycle capacity retention rate and the volume expansion rate of each battery were tested. The results can be seen in Table 1.
[0143] Table 1
[0144]
[0145] Reference Figure 2 As shown, the material in Comparative Example 3 contains only artificial graphite, and the material in Comparative Example 1 is a composite material of nano silicon powder and artificial graphite. Compared with Comparative Example 3, an additional diffraction peak appears near 30° in Comparative Example 1, corresponding to the diffraction peak of silicon. In both Example 1 and Example 2, waste silicon ingots are used as raw materials. Unlike Comparative Example 3, in Example 1 and Example 2, not only the diffraction peak of silicon appears, but also the diffraction peaks at 43° and 50° that originally belonged to the graphite material disappear. This shows that the graphite materials in Example 1 and Example 2 move along the 002 crystal plane to form graphite sheets after grinding, while the other planes gradually disappear, while this structure cannot be formed in Comparative Example 1 using nano silicon powder.
[0146] Reference Figure 3 As shown, after grinding, Example 1 and Example 2 form a structure in which graphite sheets with a length of micrometers and silicon sheets with a length of nanometers are closely attached. However, the silicon nanopowder in Comparative Example 1 is more obviously agglomerated, and does not form a structure closely attached and stacked with the graphite sheets. Comparative Example 3 only contains finely crushed graphite sheets. Figure 4 As shown, the electrode prepared in Example 1 clearly has a structure in which a silicon sheet with a thickness of nanometers and a graphite sheet with a thickness of nanometers are stacked.
[0147] As shown in Table 1, Comparative Example 2 uses a single waste silicon ingot as a silicon raw material, and the active material prepared therefrom exhibits a volume expansion rate of up to 276% during the charge and discharge process, and the cycle capacity retention rate is only 59.98%. Compared with Comparative Example 2, Comparative Example 1 mixes nano silicon powder with artificial graphite to prepare a silicon-carbon composite material, but its volume expansion rate is still 189%, indicating that the performance of the nano silicon powder cannot be significantly optimized. In addition, the initial specific capacity and capacity retention rate of Comparative Example 1 are significantly lower than those of Comparative Example 2, which may be due to the fact that the nano silicon powder is more easily pulverized and falls off. Comparative Example 3 uses a single artificial graphite as a raw material, and the volume expansion rate of the active material prepared therefrom is low, and the cycle capacity retention rate is lower than that of ordinary graphite materials, which indicates that pulverizing artificial graphite does not improve its own cycle stability.
[0148] Compared with Comparative Example 2, Examples 1 to 12 all showed significantly lower cycle capacity retention rates, indicating that grinding the silicon active material and the graphite material and forming a carbon coating layer using the preparation method disclosed in the present invention can significantly improve the volume expansion rate and cycle capacity retention rate.
[0149] Referring to Examples 1 to 7, it can be seen that the preparation method disclosed in the present invention is more suitable for scenarios where the mass ratio of silicon is relatively high. When the mass ratio of silicon to carbon is above 1.67 (i.e., 1000:600), the prepared silicon-carbon composite materials all show a cycle capacity retention rate close to or higher than 96%, and have a high reversible capacity. As the mass ratio of graphite material increases, the reversible capacity of the prepared silicon-carbon composite material decreases significantly, and the cycle capacity retention rate also decreases.
[0150] Referring to Examples 8 to 11, it can be seen that the time of fine grinding also has a certain influence on the performance of the prepared silicon-carbon composite material. When the time of fine grinding is too short, the effect of silicon-carbon composite is poor, and when the time of fine grinding is too long, the silicon-carbon is crushed too finely, which will lead to a certain decrease in the cycle capacity retention rate and the reversible capacity compared with Example 1.
[0151] Please note that the above embodiments are for illustrative purposes only and are not meant to be limiting of this document.
[0152] It should be understood that, unless otherwise specified herein, there is no strict order restriction for the execution of the steps, and the steps may be executed in other orders. Moreover, at least a portion of the steps in the preparation process may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but may be executed at different times, and the execution order of these sub-steps or stages is not necessarily sequential, but may be executed in turn or alternately with other steps or at least a portion of the sub-steps or stages of other steps.
[0153] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0154] The technical features of the above embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: The steps include: Mixing graphite material and silicon active material with a particle size of micrometers or above and grinding them to form a silicon-carbon composite material; and Placing the silicon-carbon composite material in a heat treatment chamber, introducing a carbon source gas into the heat treatment chamber, and controlling the temperature of the heat treatment chamber so that the carbon source gas is cracked to form a carbon coating layer on the surface of the silicon-carbon composite material; Among them, the step of grinding treatment includes: using sand grinding to sequentially perform coarse grinding and fine grinding on the mixed silicon active material and the graphite material, the mass ratio of the silicon active material to the graphite material is (3~10):1; in the silicon-carbon composite material formed after the grinding treatment, the thickness of the silicon active material is 1nm~200nm, the length of the silicon active material is 20nm~5000nm, the thickness of the graphite material is 1nm~200nm, and the length of the graphite material is 200nm~15000nm; the silicon active material includes single crystal silicon; the graphite material includes one or more of artificial graphite and natural graphite; in the step of grinding treatment, the fine grinding treatment time is 2h~8h.
2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: In the step of performing the grinding treatment, the time of the rough grinding treatment is 30 minutes to 120 minutes.
3. The method for preparing the silicon-carbon composite material according to any one of claims 1 to 2, characterized in that: In the step of cracking the carbon source gas, the thickness of the formed carbon coating layer is 1 nm to 20 nm.
4. The method for preparing the silicon-carbon composite material according to any one of claims 1 to 2, characterized in that: Before the carbon source gas is introduced into the heat treatment chamber, the method further includes: sintering the silicon-carbon composite material in the heat treatment chamber.
5. The method for preparing the silicon-carbon composite material according to claim 4, characterized in that: During the sintering process, the temperature of the heat treatment chamber is controlled to be 600°C~800°C.
6. The method for preparing the silicon-carbon composite material according to any one of claims 1 to 2, characterized in that: In the step of cracking the carbon source gas, the temperature of the heat treatment chamber is controlled to be 600° C. to 800° C.
7. The method for preparing the silicon-carbon composite material according to claim 6, characterized in that: The carbon source gas includes one or more of acetylene, ethylene, methane, ethane, propane and n-butane.
8. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method according to any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: Comprising the silicon-carbon composite material according to claim 8.
10. A battery, characterized in that: It comprises a positive electrode and a negative electrode which are arranged opposite to each other, and the negative electrode comprises the negative electrode sheet as claimed in claim 9.
